97.4k views
4 votes
Given f(x) = x2 - 6x and g(x) = x^3 choose

the expression for (fºg)(x).
Click on the correct answer.

Given f(x) = x2 - 6x and g(x) = x^3 choose the expression for (fºg)(x). Click on the-example-1

1 Answer

0 votes

For this case we have the following functions:


f (x) = x ^ 2-6x\\g (x) = x ^ 3

We must find
(f_ {0} g) (x):

By definition of composition of functions we have to:


(f_ {0} g) (x) = f (g (x))

So:


(f_ {0} g) (x) = (x ^ 3) ^ 2-6 (x ^ 3) = x ^ 6-6x ^ 3

Recall that by definition of power properties is met:


(a ^ n) ^ m = a ^ {n * m}

Answer:


(f_ {0} g) (x) = x ^ 6-6x ^ 3

User Nilupul Sandeepa
by
5.4k points